A New Diagnostic Criteria of Autonomic Nerve Activity measured by Plethysmograph - SHINOHARA, Kanae (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 1991)
The evaluation of heart autonomic nerve activity during quiet supine position, deep breathing position and standing position with MCV Graph Method is reported. I report age included formulae for finding M and CV of a healthy subject in quiet supine position, CV of a healthy subject in deep breathing position, and CV of a healthy subject in standing position. 1) Age included formula for finding M of a healthy subject in quiet supine position. Y=126.153-16.187*LogeX (X: age) 2) Age included formula for finding CV of a heblthy subject in quiet supine position. Y=10.818-1.993*LogeX (X: age) 3) Age included formula for finding CV of a healthy subject in deep breathing position. Y=24.293-4.738*LogeX (X: age) 4) Age included formula for finding CV of a healthy subject in standing position. Y=7.389-1.277*LogeX (X: age) When MP-P and CVP-P data measured by plethysmograph are plotted in MCV Graph, which is a quite new and obvious method, synthetic evaluation of both sympathetic and parasympathetic nerve functions is possible. Though MCV Graph Method is available for measurement under various loads, measuring requirements for plethysmograph must be filled strictly in order to get accurate data.